The impact of fires on mosquito populations in Eastern Siberian forests - Alexey V. Shvetsov (PLoS ONE, 2025)
Forest fires have a significant impact on forest fauna, killing not only mammals and birds, but also less noticeable representatives of forest fauna – insects. Existing research have mainly studied the effects on vertebrate taxa, but the data on the effects of fires on the number of insects living in forests is currently insufficient to cover all the groups. The research presented in this paper examines the immediate impact of forest fires on the number of adults in mosquito populations (Culicidae) in burned areas of the boreal forest. The data were collected in the boreal forests of Eastern Siberia, in the Republic of Sakha (Yakutia). Field survey was conducted in ten forest areas, including five recently burned and five unburned areas. Mosquitoes were caught in flight and counted during daylight hours within the time span of 7 days after the fire. We compared the data obtained from burned and unburned adjacent forest plots, which allowed us to establish the level of immediate impact of forest fires on the abundance of adult mosquito populations in the burned plots of the boreal forest. In all five pairs of forest plots, a decrease in the abundance of adult mosquitoes was noted, within the range of 86.6–93.9%. The data clearly show a lower number of adult mosquitoes for several days after the forest fire. The results obtained are of interest for further studying, regardless of the medical significance of mosquitoes, with consideration of their role in boreal ecosystems. This study is planned to be continued over the next few years in order to obtain new data on the impact of forest fires on mosquito populations in a medium and long term, which will allow us to form a broader vision of this problem.